SOSIALIASASI PENDAMPINGAN PEMBUATAN MEDIA PEMBELAJARAN BERBASIS BOARD GAME DIGITAL BAGI GURU-GURU DI PONDOK PESANTREN ROHDATUL MUSTOFA KABUPATEN TULUNGAGUNG - Nugrananda Janattaka; Nourma Oktaviarini; Aditya Pringga Satria (Kanigara, 2023)
Advances in technology have also changed the perspective in the world of education; the role of digital media has contributed to giving a new color to education. Digital media can make it easier for teachers to deliver material. The combination of digital media and educational games will have an impact on learning, thus making the learning atmosphere very enjoyable. Board games are the oldest type of game in the world, and with the progress of time, the use of digital board games is often used as a medium to attract students' interest in learning. The socialization of assistance in making digital board game-based learning media is expected to be able to provide new knowledge related to innovation in learning. This socialization was carried out twice using the genially application. The teachers were very enthusiastic about the mentoring process and were able to make and apply board games to learning in class, so they were able to make the atmosphere more interesting with innovations and board game creations from teachers at Pondok Pesantren Rohdatul Mustofa.